EVALUASI RUTE BUS RAPID TRANSIT (BRT) BERDASARKAN ASPEK KETERJANGKAUAN (STUDI KASUS: KOTA SEMARANG) - Frida Khairunisa Kundani; Yudi Basuki (Teknik PWK (Perencanaan Wilayah Kota), 2022)
The transportation system is affected by activity, movement, and network. If a transportation system is unable to keep up with the activities and movements of the community, there will be various transportation system problems such as networks. One of the problems in meeting the needs of the community movement is the uneven range of BRT services. The results of the analysis conducted by researchers based on the results of analysis of existing BRT service routes obtained that 72% of areas in Semarang city are already served, but based on the results of the analysis of brt service route recommendations obtained that 86% of areas in Semarang city are already served brt routes.. Based on the results of the study, there is 1 BRT route recommendation and 3 feeder route recommendations (PP).